2016
DOI: 10.3389/fmicb.2016.02039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Bacillus amyloliquefaciens and Bacillus subtilis Reveals Evolutional Traits for Adaptation to Plant-Associated Habitats

Abstract: Bacillus subtilis and its sister species B. amyloliquefaciens comprise an evolutionary compact but physiologically versatile group of bacteria that includes strains isolated from diverse habitats. Many of these strains are used as plant growth-promoting rhizobacteria (PGPR) in agriculture and a plant-specialized subspecies of B. amyloliquefaciens—B. amyloliquefaciens subsp. plantarum, has recently been recognized, here we used 31 whole genomes [including two newly sequenced PGPR strains: B. amyloliquefaciens N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 82 publications
2
39
0
Order By: Relevance
“…The result of biochemical tests indicated that, the selected strain can utilize majority of carbon and nitrogen sources. The previous studies specify that Saccharomyces yeast exhibit negative result in both indole and H 2 S production [19,24]. The present study also comply the same phenomenon as previous studies.…”
Section: Physiological Parameters On Growth Of B Amyloliquefacienssupporting
confidence: 93%
See 1 more Smart Citation
“…The result of biochemical tests indicated that, the selected strain can utilize majority of carbon and nitrogen sources. The previous studies specify that Saccharomyces yeast exhibit negative result in both indole and H 2 S production [19,24]. The present study also comply the same phenomenon as previous studies.…”
Section: Physiological Parameters On Growth Of B Amyloliquefacienssupporting
confidence: 93%
“…Das et.al., isolates one novel Bacillus subtilis AN11 strain from Bhitarkanika mangrove forest, Odisha, India that have strong antagonistic activity against major fish bacterial pathogens[8]. These observations suggest the involvement of Bacillus genus in responses to pathogen resistance processes.Bacillus amyloliquefaciens is a non-pathogenic soil bacteria closely related to the species B. subtilis[19]. This bacterium is gram positive rods along with peritrichous flagella consent to motility.…”
mentioning
confidence: 99%
“…GI3 was 82 482 bp in size and located at 656 129-738 610 bp in the genome, and the %G+C content of GI3 was observed to be significantly lower than the whole genome (40.1% vs. 46.1%). A genomic comparison of SQR9 with 21 other available B. velezensis strain genomes (Zhang et al, 2016) using M-GCAT showed that all of these strains have a GI inserted at the same site in their genomes, indicating a hot spot site for acquiring horizontally transferred genes. The inserted GI among these strains varied in size and gene content, with B. velezensis GYL4, B. velezensis YJ11-1-4 and B. velezensis AP183 having a shorter but comparable GI at this site, which was 78.4 Kb in GYL4 (94.7% homology) and YJ11-1-4 (94.7% homology) and 69.8 Kb in AP183 (82.5% homology) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a root colonizer, SQR9 has robust regulation systems to form a highly structured biofilm on a root surface that was found to enhance its rhizoplane colonization, during this process, the FtsEX‐CwlO pathway, two‐component regulatory system ResDE and DegUS as well as the signal bacillomycin D and oxygen deficiency were involved (Xu et al ., ; Li et al ., ; Zhou et al ., ). Strain SQR9 efficiently promotes plant growth and suppresses soil‐borne diseases (Xu et al ., , ; Qiu et al ., ), besides the antimicrobial compounds, SQR9 also benefits from its versatile metabolism that can exploit diverse root‐secreted growth substrates (Zhang et al ., , ). As with other PGPR strains such as B. velezensis FZB42, it is possible that strain SQR9 has other unidentified natural product “weapons” that contribute to its competitiveness with other rhizobacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus amyloliquefaciens: B. amyloliquefaciens is gram-positive, aerobic, and endospore-forming bacteria, which have been both widely used as producers of commercial chemicals in industry [37][38][39], and beneficial agents for plant growth promotion and suppression of soil-borne diseases in agriculture. B. amyloliquefaciens produces many metabolites such as e.g.…”
Section: Rhizobox Experimentsmentioning
confidence: 99%